Green hydrogen in the iron and steel industry increases resilience against shocks in energy prices - Nicola Leuratti; Giacomo Marangoni; Laurent Drouet; Linda M Kamp; Jan Kwakkel (Environmental Research Letters)
Geopolitical tensions and conflicts can disrupt energy markets, threatening international energy supply security and imposing financial stress on energy-intensive industries reliant on imported fossil fuels. Exploring the challenges and opportunities associated with supply diversification is crucial for understanding the potential for hard-to-abate industry decarbonization under the risk of future energy price shocks. In this context, we investigate the role of green hydrogen as a viable and sustainable alternative to natural gas applications in iron and steel manufacturing. We first quantify how the integration of green hydrogen into the existing infrastructure can complement stringent climate action ambitions in reducing CO _2 emissions over the next five decades. We find that green hydrogen acts as a transitional technology, enabling a gradual shift towards electrification of heat supply while bridging the gap until low-carbon steel technologies become commercially feasible. Furthermore, we assess the benefits of timely green hydrogen investments in mitigating the economic repercussions of unforeseen natural gas price surges. Overall, this study underscores the potential of green hydrogen in decarbonizing the iron and steel industry while promoting energy independence, but it also highlights its contingency on sufficiently ambitious climate policies and adequate technological advancements.